Factor of interfacial potential for the surface plasmon-polariton resonance sensor response - Lopatynskyi, A.M.; Lopatynska, O.G.; Poperenko, L.V.; Chegel, V.I.; Guiver, M.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
In this work, we investigate how the application of an external potential
difference to the sensitive gold-electrolyte interface influences the optical response of a
sensor based on the surface plasmon-polariton resonance (SPPR). The SPPR resonant
angle shift was registered for an aqueous solution of sulfuric acid as an electrolyte at
different potential sweep rates. From the measurements of SPPR curves versus the
applied voltage, the potential of zero charge of the gold electrode in the electrolyte
solution was estimated. To explain the external voltage influence on the SPPR sensor
response, a theoretical model was used that takes into account three factors: free electron
concentration change in the space-charge layer (SCL) in the surface layer of gold,
dependence of the capacity of electrical double layer at the interface on the voltage, and
gold film surface roughness.